A systematic review of systematic reviews on blended learning: Trends, gaps and future directions - Ashraf, M.A; Yang, M.; Zhang, Y.; Denden, Mouna; Tlili, Ahmed; Liu, J.; Huang, Ronghuai; Burgos, Daniel (Dove Medical Press Ltd, 2022)
Blended Learning (BL) is one of the most used methods in education to promote active learning and enhance students’ learning outcomes. Although BL has existed for over a decade, there are still several challenges associated with it. For instance, the teachers’ and students’ individual differences, such as their behaviors and attitudes, might impact their adoption of BL. These challenges are further exacerbated by the COVID-19 pandemic, as schools and universities had to combine both online and offline courses to keep up with health regulations. This study conducts a systematic review of systematic reviews on BL, based on PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, to identify BL trends, gaps and future directions. The obtained findings highlight that BL was mostly investigated in higher education and targeted students in the first place. Additionally, most of the BL research is coming from developed countries, calling for cross-collaborations to facilitate BL adoption in developing countries in particular. Furthermore, a lack of ICT skills and infrastructure are the most encountered challenges by teachers, students and institutions. The findings of this study can create a roadmap to facilitate the adoption of BL. The findings of this study could facilitate the design and adoption of BL which is one of the possible solutions to face major health challenges, such as the COVID-19 pandemic.
Keywords: blended learning; distance education; flipped learning; hybrid learning; literature review; research trend; Scopus; JCR